Biological and MRI Characterization of Biomimetic ECM Scaffolds for Cartilage Tissue Regeneration - Ravindran, Sriram; Kotecha, Mrignayani; Huang, Chun-Chieh; Ye, Allen; Pothirajan, Padmabharathi; Yin, Ziying; Magin, Richard; George, Anne (2015)
Osteoarthritis is the most common joint disorder affecting millions of people. Most scaffolds developed for cartilage regeneration fail due to vascularization and matrix mineralization. In this study we present a chondrogenic extracellular matrix (ECM) incorporated collagen/chitosan scaffold (chondrogenic ECM scaffold) for potential use in cartilage regenerative therapy. Biochemical characterization showed that these scaffolds possess key pro-chondrogenic ECM components and growth factors. MRI characterization showed that the scaffolds possess mechanical properties and diffusion characteristics important for cartilage tissue regeneration. In vivo implantation of the chondrogenic ECM scaffolds with bone marrow derived mesenchymal stem cells (MSCs) triggered chondrogenic differentiation of the MSCs without the need for external stimulus. Finally, results from in vivo MRI experiments indicate that the chondrogenic ECM scaffolds are stable and possess MR properties on par with native cartilage. Based on our results, we envision that such ECM incorporated scaffolds have great potential in cartilage regenerative therapy. Additionally, our validation of MR parameters with histology and biochemical analysis indicates the ability of MRI techniques to track the progress of our ECM scaffolds non-invasively in vivo; highlighting the translatory potential of this technology.